Pola Interaksi Guru Dengan Murid dalam Pembelajaran PAI di Kelas VII SMP Ali Imron Medan Tembung - Aisyah Aisyah; Jamiluddin Marpaung; Dirja Hasibuan (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This study discusses the pattern of teacher-student interaction in Islamic Religious Education (PAI) learning in grade VII of Ali Imron Junior High School, Medan Tembung. The main discussion is: What is the pattern of teacher-student interaction in Islamic Religious Education (PAI) learning at Ali Imron Junior High School, and what are the supporting and inhibiting factors in the pattern of teacher-student interaction in Islamic Religious Education (PAI) learning at Ali Imron Junior High School, Medan Tembung? This study uses qualitative research with descriptive methods and field research. Data collection for this study was sourced from Ali Imron Junior High School, Medan Tembung. The results of the field research indicate that the pattern of teacher-student interaction in Islamic Religious Education (PAI) learning in grade VII of Ali Imron Junior High School, Medan Tembung aims to introduce and familiarize students with Islamic Religious Education (PAI) learning materials. However, the success of this pattern is also influenced by several factors. There are several supporting factors, and if these supporting factors cannot be met, the opposite occurs, namely the emergence of inhibiting factors in the interaction between teachers and students. These supporting factors include the teacher's ability to master the material, manage the teaching and learning program, manage the class, and use media or resources.